Preparation and characterization of microporous magnesia‐based refractory. Issue 6 (4th August 2020) - Hou, Qingdong; Luo, Xudong; Xie, Zhipeng; Li, Yongzhi; An, Di; Li, Jijia
Abstract: In recent years, there was a huge demand for basic lightweight insulation materials in the metallurgical industry, especially magnesia‐based refractories with low thermal conductivity. Therefore, the preparation of microporous magnesia‐based refractory products through the synthesis of lightweight aggregate and the different grain compositions to meet the supply of light basic refractories is discussed in this paper. The microstructure, pore size distribution, phase composition, coefficient of thermal expansion,  thermal conductivity and sintering properties of the microporous magnesia‐based refractory products sintered at 1600°C were characterized. The results indicated that the original salt pseudomorph produced by the thermal decomposition of magnesite fine powder (porogenic agent) provides a uniform microporous structure for the synthesis of lightweight aggregates. The microporous morphology of the periclase phase was controlled by adjusting the content of the porogenic agent. The average pore size of microporous magnesia‐based refractory ranged from 1.5 to 4.2 μm, and the apparent porosity increased from 29.88% to 32.46%. In the same time, the thermal conductivity increased from 0.037 to 0.217 W/(m K), indicating that the introduction of homologous porogenic agents could produce lightweight alkaline refractories with high porosity and low thermal conductivity.